Etika Web Developer dalam Pendistribusian Pop-Up Ads pada Website - Ramdhani, Khusnun Najwa; Sari, Yuliana Mustika; Nafi', Raihan Muhammad; Firdaus Zahid, Ahmad Galvin; Fajariansyah, Ridwan; Arini, Florentina Yuni (Universitas Muhammadiyah Riau, 2024)
Globalization and the development of the internet have brought about major changes in the way information is obtained, including the use of pop-up ads as one of the increasingly popular digital marketing strategies. Pop-up ads are designed to attract users' attention with their flashy and interactive appearance. However, many users find these ads annoying as they often appear suddenly and repeatedly. In addition, pop-up ads may pose security risks in the form of malware, phishing, or malicious content that threatens users' personal data. This article analyzes the ethics of distributing pop-up ads on websites and highlights the important role of website developers in minimizing these potential risks. Through a literature review, this article asserts that website developers have a great responsibility in creating a safe, convenient, and user-oriented digital ecosystem. This includes regulating the frequency of ad appearances, creating attractive yet non-invasive designs, implementing ad due diligence, and safeguarding user privacy. By managing pop-up ads ethically, safely, and effectively, web developers can improve user experience, build trust, and prevent cybersecurity risks that harm all parties.